16 Prognostic value of high-sensitivity cardiac troponin T in patients with ST-segment-elevation myocardial infarction. (October 2018) - Khullar, N; Ibrahim, A; Saunders, J; Ahern, C; Mannix, K; Cahill, C; Kiernan, TJ
Abstract : Background: The clinical significance of high-sensitivity cardiac troponin T (hs-cTnT) following acute ST-segment-elevation myocardial infarction (STEMI) has not been well established. The aim of this study was to determine the prognostic value of hs-cTnT in the prediction of one-year mortality and repeat revascularisation in STEMI patients. Methods: Single center retrospective observational study of patients presenting with STEMI in 2016. Demographic, angiographic, and peak hs-cTnT data were obtained. The relationship between peak hs-cTnT and all-cause mortality and repeat revascularisation was examined. Results: 208 patients were included. Mean age was 63.56 years (±12.56), and 73% were males. 78 (37.5%) patients had inferior STEMI and 76 (36.5%) patients had anterior STEMI. 193 (92.8%) patients received primary percutaneous coronary intervention. Median peak hs-cTnT was 2908 ng/L (IQR: 1095, 5485) (<14 ng/L), measured at a median of 1 day from admission; median creatinine of 75 μmol/L (IQR: 68, 95). 18 (8.7%) patients died, and 35 (16.8%) had repeat revascularisation within one year. No significant relationship between peak hs-cTnT and one-year mortality (p=0.150) (figure 1) or repeat revascularisation (p=0.204) (figure 2) was found. Conclusion: Peak hs-cTnT measurements did not predict all-cause mortality or repeat revascularisation. The significance of performing routine peak hs-cTnT measurements in STEMI patients should be investigated further in larger studies.